Where Have the Monetary Surprises Gone? : The Effects of FOMC Statements - Swiston, Andrew (IMF Working Papers; Working Paper, 2007)
This paper examines the impact of central bank communication on market expectations of monetary policy and long-term interest rates by comparing Federal Open Market Committee (FOMC) action dates when a policy statement was made to dates before statements were issued. Increased communication has been associated with a reduction in the magnitude of short-term monetary surprises; a greater flow of information about the long-term path of policy that is distinct from the short-term surprise; and a larger role for these long-term surprises in the determination of long-term interest rates.